3D printing guiding stent graft fenestration: A novel technique for fenestration in endovascular aneurysm repair. (August 2017) - Huang, Jianhua; Li, Gan; Wang, Wei; Wu, Keming; Le, Tianming
Objective: To describe a novel approach, 3D printing guiding stent graft fenestration, for fenestration during endovascular aneurysm repair for juxtarenal abdominal aortic aneurysm. Methods: A 69-year-old male with juxtarenal abdominal aortic aneurysm underwent endovascular aneurysm repair with "off the label" fenestrated stent graft. To precisely locate the fenestration position, we reconstructed a 3D digital abdominal aortic aneurysm model and created a skin template covering this abdominal aortic aneurysm model. Then the skin template was physically printed and the position of the visceral vessel was hollowed out, thereby helping in locating the fenestration on stent graft. Results and conclusions: With the help of this 3D printed skin template, we fenestrated the stent graft accurately and rebuilt the bilateral renal artery successfully. This is the first clinical case that used 3D printing guiding stent graft fenestration, which is a novel approach for precise fenestration on stent graft on the table during endovascular aneurysm repair.